Effect of ploidy on growth, fillet composition and colour of large rainbow trout (Oncorhynchus mykiss) in the Black Sea - Öztürk, Dilara Kaya (Journal of Fisheries, 2024)
The purpose of this study was to determine the growth performance and fillet quality parameters of large rainbow trout (Oncorhynchus mykiss) and of different ploidy (diploid-DTS and triploid- TTS) cultured in the Black Sea. This study was carried out in a commercial fish farm in Sinop, Black Sea of Turkey. Triploid groups had a higher weight and a better feed conversion rate than the DTS at the end of the 150-day study. Crude protein and crude fat ratios were respectively higher in the DTS and TTS groups; while ploidy affected the biochemical and fatty acid compositions of the large rainbow trout, it had no effect on the amino acid compositions. The colour of fillets was affected by the crude fat ratio of the fillet. This study indicated that large rainbow trout produced in the Black Sea, regardless of its ploidy, were of high quality, nutritious and healthy for human consumption. Furthermore, it demonstrated yet again that large rainbow trout is of sufficient quality to compete with other salmonid species in the national or international markets.